JENIS DAN MAKNA KANYOUKU YANG MENGGUNAKAN ORGAN TUBUH DALAM CERPEN RASHOUMON DAN YABU NO NAKA KARYA AKUTAGAWA RYUNOSUKE - Lisdaniati, Ni Wayan Eka (Humanis; Volume 6. No. 1. Januari 2014, 2014)
This research describes the types and meaning of idiom found in Akutagawa Ryunosuke’s short story Rashoumon and Yabu no Naka. This research used the descriptive analysis method. The data were analyzed based on type of idiom theory by Hiroshi Miyaji, lexical meaning theory by Chaer, and contextual theory by Firth. It has been found 18 idioms as the result of analysis. The type of idiom from 18 data are 15 data doushi kanyouku, 2 data keiyoushi kanyouku, and one data meishi kanyouku. most of idioms do not have a well-understood lexical meaning, where as idiomatical meaning can be understood by considering the context of sentence.
Keywords: idiom, lexical meaning, idiomatical meaning